1992
DOI: 10.2166/wst.1992.0347
|View full text |Cite
|
Sign up to set email alerts
|

Peracetic Acid Disinfection of Secondary Effluents Discharged off Coastal Seawater

Abstract: Peracetic acid (PAA), a well known powerful antimicrobial agent in hospitals and in agribusiness (Fraser, 1986), has recently been used to disinfect urban effluents. It appears to be highly competitive against chlorine (Audic, 1990; Baldry, French, Slater and Desprez, 1990; Giodani, Iacoponi, Polidori, 1989), the most widely used disinfectant for sewage disposal. As PAA is a new biocide, not much quantitative data is available on its action against the faecal indicator bacteria and viruses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 0 publications
3
48
0
3
Order By: Relevance
“…The results show that PAA produced similar or even lower water genotoxic effects in comparison with the other disinfectants. This biocide, considered a good disinfectant for wastewater disinfection [Baldry et al, 1991[Baldry et al, , 1995Lefevre et al, 1992], showed lower bactericidal properties than those found for NaClO and ClO 2 in previous experiments carried out at a drinking water pilot plant [Monarca et al, 2002a]. Therefore, additional experiments with higher doses should be carried out to better evaluate the applicability of PAA for drinking water disinfection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results show that PAA produced similar or even lower water genotoxic effects in comparison with the other disinfectants. This biocide, considered a good disinfectant for wastewater disinfection [Baldry et al, 1991[Baldry et al, , 1995Lefevre et al, 1992], showed lower bactericidal properties than those found for NaClO and ClO 2 in previous experiments carried out at a drinking water pilot plant [Monarca et al, 2002a]. Therefore, additional experiments with higher doses should be carried out to better evaluate the applicability of PAA for drinking water disinfection.…”
Section: Discussionmentioning
confidence: 93%
“…For this reason it is very important to test alternative disinfectants to chlorine in order to reduce these potential health risks. Among the new disinfectants, peracetic acid (CH 3 -CO-OOH, PAA) deserves to be studied for its application in drinking water disinfection, since it is a potent antimicrobial agent and has many applications in hospitals, laboratories, and factories [Baldry et al, 1991[Baldry et al, , 1995Lefevre et al, 1992]. More recently, PAA has been found to be an effective biocidal compound for wastewater disinfection, and previous research showed that disinfection of lake and river drinking water with PAA gave rise to a very low level of genotoxicity and produced only carboxylic acids [Monarca et al, 2002a], which are not recognized as mutagenic.…”
mentioning
confidence: 99%
“…One of the currently proposed alternative disinfectants that has received particular attention over the past few years is peracetic acid (CH 3 COO 2 H; PAA). This chemical is a potent antimicrobial agent with many applications in hospitals, laboratories and factories [21][22][23]. Disinfection of drinking water from lakes and rivers with PAA results in the production of carboxylic acids, which are known to be essentially non-mutagenic, with a very low level of genotoxicity in bacterial test systems [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The disinfecting action of PAA is due to the release of active oxygen or the production of reactive hydroxyl radicals that attack the bacterial cell causing cell wall and membrane destruction as well as certain enzymes and DNA [22][23][24].…”
Section: Action Mechanismsmentioning
confidence: 99%